catena-Poly[[[diaquairon(II)]-μ-pyridine-2,5-dicarboxylato-[tetraaquairon(II)]-μ-pyridine-2,5-dicarboxylato] tetrahydrate] - Xu, Hai-Yun (International Union of Crystallography, 2008)
In the crystal structure of the title compound, {[Fe(2)(C(7)H(3)NO(4))(2)(H(2)O)(6)]·4H(2)O}(n), there are two types of coordination for the Fe(II) atoms. One Fe(II) atom is in a distorted octahedral N(2)O(4) environment, with two chelating rings from the pyridinedicarboxylate ligands and two O atoms from the water molecules, while the other is in a distorted octahedral O(6) environment with two O atoms from the pyridinedicarboxylate ligands and four O atoms from the water molecules. Both Fe(II) atoms lie on crystallographic centers of symmetry. The complex possesses an infinite chain structure running along the [101] direction. These chains are interconnected by the uncoordinated water molecules through O—H⋯O hydrogen bonds.